COW DUNG CRAFT: AN INNOVATION (WITH SPECIAL REFERENCE TO THE BHOPAL DIVISION) - Nema, Mayuri; Chauhan, Sadhana (International Journal of Research -GRANTHAALAYAH, 2026)
Craft serves as a strong foundation of human art and culture. Handicraft is an art form created by human hands, encompassing creativity, skill, and cultural consciousness. The more rich and advanced a country’s art is, the more its culture attracts global attention. Therefore, every country, region, division, and city possesses its own distinctive handicraft tradition. The present research paper focuses on the tradition of cow dung craft (Gobar Shilp) practiced in the city of Bhopal, Madhya Pradesh. Since ancient times, cow dung has been used for religious, cultural, and environmental purposes. Cow dung cakes are traditionally used for lighting the sacred fire in havan rituals, where ghee, sugar, rice, and other offerings are made. It is believed that this practice purifies the environment and increases the level of oxygen in the atmosphere. In contemporary times, artists have expanded the use of cow dung beyond its traditional religious functions and transformed it into an artistic medium. As a result, various decorative and ritual objects such as mandana designs, lamps, idols of Lord Ganesha and Lord Shiva–Parvati, cow dung plates, torans, Ram Darbar figures, garlands, small sacred fuel sticks for havan, and lamps are being created. These items are especially used during festivals like Diwali. In Bhopal, artists such as Suresh Rathore, Jitendra Rathore, Pushpa Rathore, Hukum Singh Patidar, and Neeta Deep Bajpai have been actively engaged in the field of cow dung craft for many years. Along with preserving and promoting this folk art, they have played a significant role in providing employment to women and empowering them economically. This research paper analyzes cow dung craft as a form of folk art, focusing on its relationship with folk culture, the role of artists, and its social significance.